PENGARUH TEACHER SUPPORT DAN PARENT SUPPORT TERHADAP STUDENT ENGAGEMENT DALAM PEMBELAJARAN JARAK JAUH - Meilia Trisito Anggraeni; Robert Oloan Rajagukguk; Jane Savitri (Program Studi S1 Psikologi, 2022)
Distance learning presents its own challenges for students. In the midst of these challenges, teachers and parents have a role in the learning process of the student engagement. This study aims to determine the effect of Teacher and Parent Support towards Student Engagement at the level of high school students in Bandung. The Samples came from two private senior high schools (n = 188). The Sampling is using proportionate stratified random sampling technique. The measuring instrument used is The Student Engagement Scale with a reliability of .879, The Teacher Support Scale with a reliability of .950 and The Parent Support Scale with a Chi-square value = 2181.02, df = 804, p = 0.00, RMSEA = 0.067, NFI = 0.95, CFI = 0.97, SRMR = 0.055, and GFI = 0.81. The results of the study simultaneously show that there is a significant influence between Teacher Support and Parent Support on Student Engagement. The result of this research also shows that there is an effect of Teacher Support on Student Engagement and the influence of Parent Support on Student Engagement. The support provided by teachers and parents will increase student engagement in learning activities.